Hubungan Karakteristik, Riwayat Penyakit, dan Obesitas dengan Keluhan Carpal Tunnel Syndrom (CTS) Pada Komunitas Ojek Online Wilayah Kecamatan Ciracas Jakarta Timur Tahun 2022 - Sariana, Erna; Bowo Laksono, Abdurrahman Berbudi (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
Activities involving intensive use of hands over an extended period are often associated with the occurrence of Carpal Tunnel Syndrome (CTS). According to the 2013 ILO report, CTS is consistently detected in almost every incident of work-related diseases in several countries. One type of occupation at risk of CTS is online motorcycle taxi drivers. The aim of this study is to determine the relationship between characteristics, medical history, and obesity with CTS complaints in the Online Motorcycle Taxi Community of the Ciracas District, East Jakarta, in the year 2022. The study design is cross-sectional. The sample consists of 107 online motorcycle taxi drivers from the Ciracas District. The research was conducted from April to September 2022. Data collection was done using questionnaires. Data analysis included univariate, bivariate (Chi-square test), and multivariate (Logistic Regression test). The research findings reveal that respondents with CTS complaints in the at-risk category are 29.9%. The majority of respondents are below 40 years old (52.3%), have a work experience of less than 4.5 years (51.4%), work for more than 8 hours per day (59.8%), have no medical history (59.8%), and are not obese (71.0%). The bivariate analysis results show that variables significantly associated with CTS complaints include work experience (p = 0.012 and OR = 3.3), work duration (p = 0.021 and OR = 3.297), medical history (p = 0.046 and OR = 2.571), and obesity (p = 0.049 and OR = 2.654). The multivariate analysis results indicate that there is no single dominant factor with the highest influence on CTS complaints within the online motorcycle taxi community (p > 0.05). The recommendation is to provide Health Education to online motorcycle taxi drivers regarding preventive measures for CTS complaints. This aims to help them manage their work schedule effectively and take preventive actions against CTS issues, such as regular breaks, supportive nutrition, and so forth. Keywords: characteristics, medical history, obesity, Carpal Tunnel Syndrome (CTS) complaints, Online Motorcycle Taxi